2021
DOI: 10.3389/fpubh.2021.723613
|View full text |Cite
|
Sign up to set email alerts
|

Health Systems Responsiveness in Addressing Indigenous Residents' Health and Mental Health Needs Following the 2016 Horse River Wildfire in Northern Alberta, Canada: Perspectives From Health Service Providers

Abstract: Following the 2016 Horse River Wildfire in northern Alberta, the provincial health authority, the ministry of health, non-profit and charitable organizations, and regional community-based service agencies mobilized to address the growing health and mental health concerns among Indigenous residents and communities through the provision of services and supports. Among the communities and residents that experienced significant devastation and loss were First Nation and Métis residents in the region. Provincial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Where DID it t represents the year t of the implementation of carbon emission trading policy in province or city i. The remaining variables are explained in the same way as for model (7). The sample observation period of this paper is 2009-2020, covering 4 years before the implementation of the policy and 6 years after the implementation of the policy in some provinces and cities.…”
Section: Model For Parallel Trend Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Where DID it t represents the year t of the implementation of carbon emission trading policy in province or city i. The remaining variables are explained in the same way as for model (7). The sample observation period of this paper is 2009-2020, covering 4 years before the implementation of the policy and 6 years after the implementation of the policy in some provinces and cities.…”
Section: Model For Parallel Trend Testmentioning
confidence: 99%
“…Ke and Chen ( 6 ) based on the Health Belief Model, found that residents are living healthier lifestyles after the COVID-19 pandemic in Wuhan, China. Fitzpatrick et al ( 7 ) showed that aboriginal health and mental health problems were more severe in the wake of 2016 Horse River Wildfire in Northern Alberta, Canada. Li et al ( 8 ) claimed that participating in physical exercise can significantly improve the subjective and objective health level of individuals.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Several regions have successfully identi ed and addressed disaster recovery issues through community-based approaches [5]. Globally, the importance of and need for community-based research is increasingly recognized in the context of disasters such as Iraq con ict [6], landslides [7], oods [8], hurricanes [9][10][11], and bush res [12,13]. By contrast, in the Japanese context, awareness of the importance of CBPR has increased since the 2011 Great East Japan Earthquake [14,15] and has been reported in relation to the Kumamoto earthquake [16] and oods [17] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health is known to affect vulnerable populations after disasters. A health impact survey conducted after the Horse River wildfire in Alberta, Canada reported that adolescents who had experienced previous trauma and mothers who were pregnant or postpartum had higher rates of mental illness following the disaster [ 12 , 13 , 14 , 15 ]. Therefore, we assessed whether residents with previous poor mental health were more adversely affected when exposed to a chemical disaster.…”
Section: Introductionmentioning
confidence: 99%